Crack growth modeling for mixed-mode problems - Cisilino, Adrian Pablo (2010)
This paper presents a review of the dual boundary element method for modeling crack growth in two-dimensional and three-dimensional mixed mode problems. The modeling strategy for crack coalescence using the DBEM is pre- sented and comparisons are made with alternative solutions where available. Also presented are three-dimensional multiple crack growth and microcrack growth prob- lems.